Neurointerventional Research between 2003 and 2012: Slow Growth, High Interdisciplinary Collaboration, and a Low Level of Funding - Lee, J.Y.; Yoon, D.Y.; Yoon, S.D.; Nam, S.A.; Cho, B.M. (American journal of neuroradiology : AJNR, 2014)
Neurointerventional therapy of cerebrovascular disease is a greatly expanding field across many specialty disciplines. The goal of this study was to analyze the characteristics and trends of scientific publications that focused on neurointervention during the past decade. A bibliometric evaluation of neurointerventional research published between 2003 and 2012 was conducted by using the PubMed data base. Analyzed parameters included the year of publication, type of document, language of the article, topic, declared funding, country of origin, type of collaboration between disciplines, the first author's specialty, and subject category and the Impact Factor of the publishing journal. Between 2003 and 2012, a total of 2123 articles were published, of which 1107 (52.1%) were original articles, 1948 (91.8%) were written in English, 192 (9.0%) received funding, 661 (31.1%) were published by the United States, and 1060 (49.9%) resulted from interdisciplinary collaboration. Neurosurgery departments produced the most articles (n = 910, 42.9%), followed by radiology (n = 747, 35.2%) and neurology (n = 270, 12.7%). The time-trend analysis in the number of publications demonstrated slow growth from 2003 to 2012, with an average annual growth rate of +6.0%. The fields of neurosurgery, radiology, and neurology have contributed substantially to neurointervention research. Slow growth, high interdisciplinary collaboration, and a low level of funding are peculiar characteristics of research in this field.